The Role of Intelligence in Countering Radicalism Threats within the Ranks of the Indonesian National Army (TNI AD) - Jadmiko, Adi; Supriyadi, Supriyadi; Prasetyono, Budi (Pusat Studi Politik dan Kebijakan Strategis Indonesia (POLKASI), 2025)
Pancasila plays a role in maintaining national stability which can be achieved if the Indonesian people feel safe and peaceful and the integrity and sovereignty of the Indonesian state are protected from internal and external threats. Radicalism and terrorism are internal threats. Exposure to radicalism can cause a person to commit acts of terrorism. According to the data, it is known that the perpetrators of acts of radicalism and terrorism consist of the unemployed, unskilled workers, independent entrepreneurs, employees/employees, professionals, civil servants, public officials and the military. This research will examine how the role of intelligence in dealing with the threat of radicalism among Indonesian Army soldiers. The research method used is a qualitative approach. The results of the study show that the threat of radicalism among TNI AD soldiers is a real threat and there are 5 (five) TNI AD soldiers who are exposed to radicalism and are involved in criminal acts of terrorism. The exposure of TNI AD soldiers to radicalism is caused by internal and external factors, such as ideology and the economy. The role of intelligence to prevent this can be in the form of monitoring, close surveillance and profiling strategies for Indonesian Army soldiers. Apart from that, it was also carried out in the form of emphasis in the form of issuing a telegram from the TNI Commander regarding the prevention of radicalism and cooperation in preventing and overcoming radicalism with the BNPT and related agencies through the SKB 11 Ministers. The detection of TNI AD soldiers who were exposed to these radical views was through identifying symptoms of radicalism in TNI AD Soldiers by searching for evidence in the form of profiling them. Besides that, the internal situation of the institution was restored. After carrying out the detection, security is carried out in a preventive form by screening all TNI soldiers as well as security in a repressive form by efforts to develop mentality, deradicalization, and socialization of planting Pancasila ideological values.